Green synthesis of zinc oxide nanoparticles using brown algae on oil palm empty fruit bunch pulp and paper substrates: effect of pH 6 to 8 - Sobri, Zakiah; Mohamed Asa’ari, Ainun Zuriyati; Mohd Azib, Muhammad Azri; Mohd Nazri, Muhammad Irdin; Zainal Abedin, Nur Hanani; Zainudin, Edi Syams (North Carolina State University, 2025)
Green synthesis in producing zinc oxide nanoparticles is well known for its ecofriendly nature and acceptable cost. This study determined the effect of pH 6 to 8 on the green synthesis of zinc oxide nanoparticles using brown algae on oil palm empty fruit bunch pulp (OPEFB) and paper substrates. Ten samples including blank samples were prepared. Brown algae extract was prepared followed by preparation of pulp and paper from commercial OPEFB sheets. The brown algae were set at 3 pH levels, 6 (blank sample), 7 and 8. The PU samples underwent handsheet making based on TAPPI Standard T205, while the PA samples were air-dried prior to testing. All samples were analyzed via FESEM, EDX, and XRD, which confirmed that zinc oxide nanoparticles were successfully synthesized on pulp and paper surfaces. It was shown that higher pH levels enhanced the synthesis performance of zinc oxide nanoparticles, and 70 °C was the optimal temperature. The nanoparticles size obtained in this study were 0.27 to 0.54 nm and 0.51 to 1.05 nm for green-synthesized PU and PA samples respectively. Green synthesis was observed to operate better on pulp fiber surfaces rather than paper surfaces.